2020
DOI: 10.1111/tbj.14046
|View full text |Cite
|
Sign up to set email alerts
|

Association of patient factors with time to treatment for breast cancer

Abstract: Background Studies have shown that in the United States, there is an increasing time from breast cancer diagnosis to first treatment (time to treatment or “TTT”), with concern that such delays may worsen oncologic outcomes. A component of TTT is the time from the initial diagnosis to initial surgical consultation (SC). We sought to identify patient‐related factors associated with time to initial SC, and evaluate how this interval is associated with overall total time to treatment (TTT). Methods A prospective d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
(26 reference statements)
0
4
0
Order By: Relevance
“… 27 Additionally, patients do not always choose the first available appointment due to personal scheduling conflicts or other concerns. 28 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 27 Additionally, patients do not always choose the first available appointment due to personal scheduling conflicts or other concerns. 28 …”
Section: Discussionmentioning
confidence: 99%
“…27 Additionally, patients do not always choose the first available appointment due to personal scheduling conflicts or other concerns. 28 NQMBC centers were polled by the NCBC in 2021 regarding methods to improve timeliness. Strategies used by centers to decrease time included adding open time slots, improving office organization, sharing timeliness data at breast conference, meeting with pathology to assess turnaround times, and optimizing the phone tree and front office.…”
Section: Discussionmentioning
confidence: 99%
“…We found that compared to patients with private insurance, those who were Medicare insured had 27% higher odds of delayed treatment. Treatment delays seen in patients with Medicare coverage may be due to age related factors, as older age was a patient‐related factor shown to increase time to treatment 42 . A study found moderate delays in breast cancer treatment to occur more frequently in older patients, however longer delays were not common 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Treatment delays seen in patients with Medicare coverage may be due to age related factors, as older age was a patient‐related factor shown to increase time to treatment. 42 A study found moderate delays in breast cancer treatment to occur more frequently in older patients, however longer delays were not common. 43 Compared to patients who were privately insured, Medicaid enrollees had 75% higher odds of delayed treatment, higher than the odds for Medicare enrollees.…”
Section: Discussionmentioning
confidence: 99%